535. Transmission of Clostridium difficile (CD) From Patients ≤2 Years of Age in a Pediatric Oncology Setting. (26th November 2018) - Robilotti, Elizabeth; Chow, Hoi Yan; McMillen, Tracy; Huang, Weihua; Chen, Donald; Babady, N Esther; Kamboj, Mini
Abstract: Background: Testing for Clostridium difficile (CD) is not recommended in patients under 2 years old because of CD endemicity in young children and absence of associated disease. These patients may, however, represent a reservoir for CD transmission to other high-risk pediatric patients. We describe the strain relatedness of CD isolates among a cohort of pediatric oncology patients by multilocus sequence type (MLST) and interrogate putative transmission events originating from donors ≤2 years of age with whole-genome sequencing (WGS). Methods: Demographic and epidemiologic information was extracted from our infection control database for all laboratory identified CD cases in pediatric patients from October 2014 to December 2017. Patients ≤2 year old were identified as potential CD donors in a temporal–spatial model of transmission based on initial MLST analysis. CD recipients were identified as any patient with overlapping hospitalization within 12 weeks of the donor, regardless of recipient's age. Donor–recipient pairs were further characterized with WGS to investigate the validity of presumed transmission events by epidemiologic links and MLST. Results: During the study period CD infection (CDI) was diagnosed in 179 unique pediatric patients. Thirty-nine were ≤2 years. Overall MLST distribution of strains and frequency among patients ≤2 years is shown in Figure 1. ST-2 and 42 were the dominant strains (32% total). ST-11 was not isolated among ≤2 years group and only two ST-1 were isolated without identification of any related recipient cases. Based on concordant strain type on initial MLST, 27 (69%) patients ≤2 years of age were identified as potential donors to 48 pediatric patients; 40 samples were recoverable for WGS representing seven donors and 33 recipients. Despite the high concordance on MLST, WGS revealed only one pair of related CD isolates among these based on a single nucleotide polymorphism (SNP) difference of 1. Retrospective review revealed that these patients were in adjoining rooms during an overlapping admission but were diagnosed with CDI 7 days apart. Conclusion: In a pediatric oncology unit, hospitalized children ≤2 years of age are not a substantial reservoir for hypervirulent or epidemic strains and an infrequent source of transmission to others with spatial proximity. Disclosures: All authors: No reported disclosures.